Plurality of Identities in Europe - Greab, Carmen Gabriela (Politikon: The IAPSS Journal of Political Science, 2006)
The European Union differs from the traditional states not only due to its external policies or internal institutional design, but also due to its claim to act as a single and unitary actor. Moreover, if we look within European Union, some of the member states are many times rivals for the EU as actors in the international arena. In this context, the present article is trying to analyze this difficulty of European Union to be a unitary international actor from a more recent approach to international relations, that of identity.